FACTORS INFLUENCING RESILIENCE OF PRIMARY SCHOOL TEACHERS, HULU LANGAT, SELANGOR - Hui, Tho Mei; Abdullah, Zuraidah (Universitas Pendidikan Indonesia, 2020)
This study aimed to explore the factors influencing resilience of primary school teachers, Hulu Langat, Selangor. The research design used in this study is quantitative, and survey question is used to collect the data. A total of 351 respondents is randomly selected. Research findings are analysed using statistical descriptive and inferences. Findings show that the level of teachers’ resilience (M=3.92, SD=.44) are high. The mean score of each dimension is personal competence (M= 3.77, SD =.57), social competency (M=3.99, SD=.55), social resource (M=3.85, SD=.54), family cohesion (M= 4.20, SD= .65) .and structure style ( M= 3.77, SD = .48). This study helps teachers to improve their resiliency, enables them to remain in the teaching profession and commits to the job which was assigned to them.